The thermal accommodation of helium and argon on hot tungsten - Watts, M; M. J. Watts (1977)
﻿ Experiments are described in which the momentum flux of gas atoms, remitted normal to the surface of a hot clean tungsten ribbon immersed in a low pressure of helium or argon, is measured with a torsion balance and the thermal accommodation coefficient deduced. Data are presented in which the tungsten temperature range was 700 to 1900 K for helium and 1100 to 1700 K for argon. If it is assumed that the normal remitted momentum flux is that expected on assumption of the cosine emission relation, accommodation coefficients much larger (and for argon physically impossible) than those found previously by other workers are implied. A model is proposed which assumes that atoms impinging on and remitted from the hot tungsten ribbon conserve momentum in directions parallel to the surface. This results in a remitted flux, in the direction of the normal, greater than the cosine relation would predict. The resulting accommodation coefficients are then of the same order as those found using the total heat loss method. The method here reported is believed to be novel. Its accuracy increases with the temperature of the hot solid. It permits the measurement of translational thermal accommodation without relying on the temperature coefficient of resistance of the solid and hence is applicable to alloys and to non-metals. For metals., which have a normal temperature coefficient of resistance, the method allows translational accommodation to be measured and internal energy accommodation to be deduced.